Penerapan Sistem Terdistribusi Absensi Karyawan Berbasis Android Guna kedisiplinan pada Karyawan CV Buana Utama - Tertia, Farhan Adhimukti; Hetty Rohayani; Helmina Helmina; Dani, Rian (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
CV Buana Utama is a company that distributes frozen sea fish. The employee attendance system at CV Buana Utama, which includes information about entry times, picket schedules and attendance reports, is still done manually. So, during the recording process, errors may occur, or reports may be less accurate, and it may take longer to find the required data. This research utilizes the waterfall method. This Android-based application will make the employee attendance system better than the manual system so that employees are more time disciplined and work runs more efficiently. Apart from that, the best solution is to use an Android system that can solve company problems and achieve company goals.